Immunogenicity of the biosimilar CT-P13 infliximab or the original infliximab in Iraqi patients with Ankylosing spondylitis does not correlate with their demographic characteristics - M. Kamil, Mohammed; Jabarah, Mohammed Abdul- Hassan; A.l. Jasim, Nizar (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Ankylosing spondylitis is a rare disease affecting people with hereditary factors. Its treatment includes life style modification and use of drugs such as the biologic agent infliximab or its biosimilar, CT-P13 infliximab. Despite their therapeutic usefulness, these agents are associated with a number of serious adverse effects such as immunogenicity.Objectives: The aim of current study was to investigate if immunogenicity of the biosimilar CT-P13 infliximab or the original infliximab, in Iraqi patients with Ankylosing spondylitis, is affected by any of the patients’ demographic characteristics.Methods: A retrospective open-label study was conducted from December 2021 to March 2022 at the Rheumatology Unit, Baghdad Teaching Hospital/Medical City, Baghdad. Forty-four patients were taking Infliximab, and another 50 patients were taking CT-P13, both at a dose of 5mg/kg for 3 months prior to recruitment in current study. Disease activity was assessed by ASDAS-CRP score while antibodies and C-reactive protein were tested by Enzyme-Linked Immunosorbent Assay technique. Statistical analyses were performed using SPSS statistical package for Social Sciences version 20.0. The level of significance was considered at P0.05). Similar data were reported regarding the biosimilar CT-P13 infliximab except for smoking and disease activity which exhibited significant correlation with development of anti-CT-P13 antibodies (P